Extracellular electron transfer mechanisms between microorganisms and minerals - Shi, Liang; Dong, Hailiang; Reguera, Gemma; Beyenal, Haluk; Lu, Anhuai; Liu, Juan; Yu, Han-Qing; Fredrickson, James K. (Nature reviews. Microbiology, 2016)
Key Points Specific microorganisms use metal-containing minerals as electron sinks for heterotrophy-based respiration and electron and/or energy sources for autotrophic growth. The microbial cell envelope is an electrical and physical barrier that can be overcome by pathways that consist of redox proteins (for example, c -type cytochromes) and structural proteins, which span the entire width of the microbial cell envelope and enable the exchange of electrons with extracellular minerals. Some microorganisms can extend their redox-active surface beyond the confines of the cell envelope by forming microbial nanowires, which transfer electrons to distal minerals. c -Type cytochromes, microbial nanowires and other cellular structures are, or are suggested to be, involved in intercellular electron transfer between the same or different species or even domains. Minerals that contain metal ions can also function as electrical conductors and batteries to facilitate electron exchange among different groups of microorganisms. Microorganisms with extracellular electron transfer capabilities have been harnessed for the bioremediation of environmental contaminants, the production of biofuels, the production of nanomaterials with novel properties and biomining of copper, gold and other metals. Microorganisms with electron transfer capabilities, such as metal-reducing microorganisms, use specialized systems to exchange electrons between minerals and cells. In this Review, Shi et al . summarize the underlying molecular mechanisms, such as cytochromes and nanowires, and biotechnological applications. Electrons can be transferred from microorganisms to multivalent metal ions that are associated with minerals and vice versa. As the microbial cell envelope is neither physically permeable to minerals nor electrically conductive, microorganisms have evolved strategies to exchange electrons with extracellular minerals. In this Review, we discuss the molecular mechanisms that underlie the ability of microorganisms to exchange electrons, such as c -type cytochromes and microbial nanowires, with extracellular minerals and with microorganisms of the same or different species. Microorganisms that have extracellular electron transfer capability can be used for biotechnological applications, including bioremediation, biomining and the production of biofuels and nanomaterials.